CHALLENGES TO QUALITY ASSURANCE IN TEACHER EDUCATION AND THE WAYS FORWARD IN NIGERIA - AKOGUN, Alabelapo Kadri; SUBAIR, Bashirat Olanike (Ilorin Journal of Education, 2023)
Education is the key to the development of any nation therefore, to make teacher education in Nigeria to be qualitative like the developed nations, there was the need to eliminate the challenges that threatened Quality Teacher Education so that educational goals and objectives could be achieved. Poor quality teaching resulted mostly from untrained teachers that passed on their ignorance to the students. No nation education can rise above the quality of its teachers. Historical methods of research were used to examine the concept of Quality Assurance (QA) and Teacher Education (TA), challenges to quality teacher education, and ways to end the challenges so that desired quality teacher education in Nigeria could be achieved. These challenges included inadequate funding, inadequate education statistics, the politicization of educational matters, the proliferation of mushroom schools, the problem of insecurity, and poor salary and welfare package for teachers. Suggested ways to overcome these challenges were adequate to fund should be allocated to education in the annual budget preparation and cash-backed, employment of professional qualified teachers and prepared the teachers to become expert practitioners, by transforming and overhauling of teachers’ preparation such as mandatory induction programme for new teachers, mentorship, training and retraining of teachers and so on. Teaching and learning environments are made conducive and end to all forms of insecurity in the land, regular payment of teachers’ salaries in addition to special welfare package to attract brains to the profession. conclusively, the government at all levels should give their total support and commitment to teacher education that the nation’s education could be among the best in the committee of developed nations. Conclusively, despite all the challenges to teacher education in Nigeria, graduates at all levels of education were able to compete favourably with their counterparts all over the world.